Household Transmission of Community-Associated Methicillin-Resistant Staphylococcus Aureus - Zhu, Feiteng; Zhuang, Hemu; Ji, Shujuan; Xu, Er; Di, Lingfang; Wang, Zhengan; Jiang, Shengnan; Wang, Haiping; Sun, Lu; Shen, Ping; Yu, Yunsong; Chen, Yan (Frontiers in Public Health, 2021)
Currently, the community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) transmission mechanism is unclear but must be considered in conjunction with the asymptomatic S. aureus strains colonization dynamics. This epidemiological study aimed to determine household role in CA-MRSA transmission in China. Five patients with culture-confirmed CA-MRSA infection and five control patients were recruited from the Sir Run Run Shaw Hospital in Zhejiang, China, between December 2019 and January 2020. The household members of the patients, their pets, and environmental surfaces were sampled and screened for MRSA colonization. Mass spectrometry identification and antimicrobial susceptibility testing were performed on the MRSA isolates. Whole-genome sequencing and core genome multilocus sequence typing (cgMLST) were performed to determine the origin and transmission of MRSA isolates in the households. Overall, 14 S. aureus-positive specimens (14.1%, 14/99) were obtained from the five households of patients with CA-MRSA infections, of which 12 (85.7%) were MRSA. The overall positivity of MRSA was 12.1% (12/99) among the samples from the CA-MRSA households, while no MRSA isolates were detected in the five control households. Most MRSA isolates belonged to epidemic CA-MRSA clones, such as ST59 (15/35, 42.9%) and ST508 (15/35, 42.9%). The cgMLST results confirmed that MRSA was transmitted among patients, contacts, and pets in the households and was present on environmental surfaces in the CA-MRSA patients’ households. In conclusion, the study showed that the home environment was an important MRSA reservoir. Therefore, focusing on MRSA decolonization for patients alone is not sufficient for infection control of CA-MRSA.